Optical Coherence Tomography: An Adjunctive Tool for Differentiating between Choroidal Melanoma and Metastasis - Vicktoria Vishnevskia-Dai; Dinah Zur; Shiran Yaacobi; Iris Moroz; Hadas Newman; Meira Neudorfer (Journal of Ophthalmology)
Purpose. To investigate the value of optical coherence tomography (OCT) for differentiation between choroidal melanoma and metastasis based on characteristics of the anterior choroidal surface and the chorioretinal interface. Methods. This retrospective observational case series included 29 patients with untreated choroidal melanomas and 21 patients with untreated choroidal metastases. Regularity and lobularity characteristics of the anterior choroidal surface were evaluated in a masked manner. Retinal and retinal pigment epithelium (RPE) findings were documented as well. Results. OCT demonstrated a regular and smooth anterior choroidal surface in 89.7% of the eyes with melanoma and in 47.6% of the eyes with metastasis (p=0.002; sensitivity = 89.7%; specificity = 52.4%). The anterior choroidal contour was lobulated in 81.0% of the eyes with metastasis versus 17.2% of the eyes with melanoma (p<0.001; sensitivity = 82.8%; specificity = 81.0%). RPE thickness and neuroretinal characteristics (e.g., retinal thickness, the presence of cysts, and the presence of subretinal fluid) were similar in both choroidal tumors. Conclusion. OCT may serve as a noninvasive adjunctive tool for the differential diagnosis of choroidal tumors. Choroidal melanomas usually demonstrate regular surfaces on OCT, while choroidal metastases usually have an irregular and lobulated surface.